Family Structure Change Among Latinos: Variation by Ecologic Risk. (October 2019) - Cabrera, Natasha J.; Karberg, Elizabeth; Fagan, Jay
We examined differences in family structure change in an urban sample of mothers ( N = 1, 314) from their child's birth to age 5 and whether ecological risk moderated this association. We found that compared with U.S.-born Latino mothers, foreign-born Latino mothers were 62% less likely to break up and 75% less likely to repartner than remain stably resident. Across nativity status, Latina mothers with fewer children, more economic stress, less income, and less frequently reported father involvement were more likely to break up and repartner than remain stably resident. We found no moderation effects of ecological risk.